Development of Numerical Literacy-Based Student Worksheet on Improving Mathematical Reasoning - Lisa Purwanti; Eko Darmanto; Sumaji (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The study background is that students' mathematical reasoning abilities must be improved through learning. Efforts to improve mathematical reasoning are carried out with the Numerical Literacy-Based Student Worksheet Development process. The worksheet (LKS) development process must meet the eligibility to support learning. The study method uses Research and Development that includes ten steps—data collection techniques with interviews, questionnaires, and tests. The research subjects were fourth-grade elementary school students. The study results found that development begins with preliminary studies, analysis, formulation of learning media development, media design, prototypes, and instrument development. The validation of media experts scored 91.4% and material experts 80% with a valid predicate. The teacher's response questionnaire results were 84.2% in the very decent category, and the students’ response questionnaire got 83.6% in the very like category. The results of the validity test of mathematical reasoning are valid because the value of r-count > r table (0.632). The reliability test obtains an alpha value of 0.979, which indicates the instrument is reliable. This study concludes that the Development LKS based on numerical literacy meets the needs analysis of students and teachers and obtains valid criteria from media and material experts. The development of numerical literacy-based student worksheets (LKS) also received good grades for improving students' mathematical reasoning.